2017
DOI: 10.1111/cei.13077
|View full text |Cite
|
Sign up to set email alerts
|

Activation of plasmacytoid dendritic cells by apoptotic particles – mechanism for the loss of immunological tolerance in Sjögren's syndrome

Abstract: Sjögren's syndrome (SS) is a common autoimmune disease targeting salivary and lacrimal glands. It is strongly female-dominant, characterized by low oestrogen levels combined with a local intracrine dihydrotestosterone defect. We hypothesized that these hormonal deficits lead to increased apoptosis of the epithelial cells and plasmacytoid dendritic cell (pDC)-mediated proinflammatory host responses. Expression of Toll-like receptors (TLRs)-7 and -9 and cytokine profiles was studied in pDCs treated with apoptoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 36 publications
(63 reference statements)
0
48
0
1
Order By: Relevance
“…Moreover, a recent study showed that apoptotic cells can release MVs and exosomes in addition to ApoBDs 57 . Apoptotic MVs (0.2-1 µm in diameter), also called apoptotic microparticles, are presumed to be synthesized by plasma membrane budding in apoptotic processes and are known to induce proinflammatory cytokines through the transfer of their cargo to recipient dendritic cells or to suppress the immune system 43,[58][59][60] .…”
Section: Apoptotic Extracellular Vesiclesmentioning
confidence: 99%
“…Moreover, a recent study showed that apoptotic cells can release MVs and exosomes in addition to ApoBDs 57 . Apoptotic MVs (0.2-1 µm in diameter), also called apoptotic microparticles, are presumed to be synthesized by plasma membrane budding in apoptotic processes and are known to induce proinflammatory cytokines through the transfer of their cargo to recipient dendritic cells or to suppress the immune system 43,[58][59][60] .…”
Section: Apoptotic Extracellular Vesiclesmentioning
confidence: 99%
“…An earlier investigation showed that apoptotic particles induced TLR-7 and TLR-9 expression in pDCs in vitro [18]. Although our prior study demonstrated that TLR-3 signal activation induced apoptosis in SGECs from individuals with pSS [9], it is not yet known whether stimulation of the TLR-7 signaling pathway induces apoptosis.…”
Section: Discussionmentioning
confidence: 72%
“…Our earlier investigation demonstrated the expression and function of TLR-2-4 in patients with SS [15], and in the present study we focused on TLR-7-9 from the viewpoint of receptors of nucleic acid sequences of viruses and/or self-antigens. Several studies showed that TLR-7-9 are expressed in PBMCs from SS patients [6,16,17] and one study suggested that apoptosis induced TLR-7 and -9 expressions in pDCs [18]. However, the expression of TLR-7-9 in salivary glands has not been well investigated.…”
Section: Discussionmentioning
confidence: 99%
“…However, with the development of detection technology, researchers have found smaller vesicles ( Simpson and Mathivanan, 2012 ) produced by dying cells in addition to traditional apoptotic bodies. Although there is no well-defined criteria to distinguish ApoBDs from other ApoEVs, the vesicles can be classified by diameter: larger membrane-wrapped vesicles termed ApoBDs/ABs have diameters of 1000–5000 nm ( Atkin-Smith et al, 2015 ), and the smaller vesicles termed apoptotic microvesicles (ApoMVs) or exosome-like ApoEVs ( Park et al, 2018 ) have diameters of 50–1000 nm ( Schiller et al, 2012 ; Ainola et al, 2018 ). Lacking standard classification makes it difficult to draw accurate conclusions on the functions of ApoEVs.…”
Section: Apoptotic Cell-derived Extracellular Vesiclesmentioning
confidence: 99%